إمكانية تبني مهارات التسويق الإبتكاري لتعزيز ريادة منظمة الأعمال دراسة ميدانية في شركة Sweetlé بمدينة الجلفة-الجزائر (Revue El-Wahat pour les Recherches et les Etudes, 2015)
the  goal behind this research paper is to identify the innovative marketing skills and to what extent they do exist in the target business organisation, in order to see how it helps in the business organisation to be in the Entrepreneurship throughout the practice in sweetle factory in Djelfa - Algeria.   therefore, some hypotheses were there to  realize the research objectives, (36) questionnaires were distributed among executives in the target  business organisation and all of them (100%) were replied, then  the hypotheses of this research paper  were tested by the analysis of the combination and the affect using set of statistical signals with the help of the statistic programme (SPSS,V17). this research paper comes out with some conclusions, the most important one is that the  innovative marketing skills (to determine the problem, flexibility, originality, struggle and the capacity of effective contact) that sweetle business organisation believe in helps this organisation to be in the Entrepreneurship (take risks, creativity and competition). thus ,some recommendations and suggestions were derived hoping that those who are considered with in the field benefit from. key words: creative marketing, skills, Entrepreneurship, business organisation, sweetle factory, Djelfa.